Load Balancing On Mikrotik at Karang Jaya Health Center Using NTH Method - Agil Homsi Syahrani; Boy Yuliadi (LPPM Universitas Islam 45 Bekasi, 2023)
Communication needs are very important along with the progress and development of today's communication technology. This requires better network capabilities to handle large data traffic and improve access speed and quality. Karang Jaya Health Center only uses 1 ISP as the main running internet network. The network often experiences downtime and slowness because quite a lot of clients use the network. Applying the nth method of load balancing techniques is a solution to maintaining the quality of the internet network at the Karang Jaya Health Center. The research method for implementing the nth load balancing method is divided into two, namely the data collection method consisting of the stages of Observation, Interview, Documentation, and Literature Study. As well as the development method, namely the Analysis Stage, Design Stage, Simulation Stage, Implementation Stage, Monitoring Stage, and Management Stage. After configuring the nth load balancing method on the proxy device at the UPTD Karang Jaya Health Center, it was found that the traffic results from the division of the two ISP lines were active and the traffic load was divided evenly so that overloads could be avoided. Distribution of traffic load is prioritized by seeing which ISP is not busy with greater bandwidth speed. As well as managing bandwidth can optimize the performance of the internet network at the Karang Jaya Health Center.